3d transition metal complexes with a julolidine–quinoline based ligand: structures, spectroscopy and optical properties. Issue 2 (15th December 2015) - Fanna, Daniel J.; Zhang, Yingjie; Li, Li; Karatchevtseva, Inna; Shepherd, Nicholas D.; Azim, Abdul; Price, Jason R.; Aldrich-Wright, Janice; Reynolds, Jason K.; Li, Feng
Abstract : Five new complexes of a julolidine–quinoline based ligand with 3d transition metals have been synthesised and structurally characterised. Abstract : A Schiff base type ligand with the combination of the julolidine and the quinoline groups has been reported as a potential chemosensor in detecting the cobalt(ii ) ion among other heavy and transition metal ions in solution. However, no crystal structure of such a ligand with any metal ions has been reported. In this work, its complexation with 3d transition metal ions (Mn(ii ), Co(ii ), Ni(ii ), Cu(ii ) and Zn(ii )) has been investigated with five new complexes being synthesised, and spectroscopically and structurally characterised. [Mn2 L 2 (CH3 OH)2 (CH3 COO)2 ]·CH3 OH (1 ) {HL (C22 H21 N3 O) = (( E )-9-((quinolin-8-ylimino)methyl)-1, 2, 3, 5, 6, 7-hexahydropyrido[3, 2, 1- ij ]quinolin-8-ol)} shows a dinuclear structure with two Mn : L  : acetate (1 : 1 : 1) units bridged by two methanol molecules. [CoL 2 (NO3 )]·CH3 OH·H2 O (2 ) and [NiL 2 ]·H2 O (3 ) exhibit mononuclear structures with a Co : L or Ni : L ratio of 1 : 2. [CuL (CH3 COO)]·1/3CH3 OH (4 ) demonstrates a mononuclear structure and the Cu ion has a square planar coordination polyhedron with aL ligand and a highly non-symmetrical acetate anion. [Zn2 L 2 (CH3 COO)2 ]·CH3 OH (5 ) has two types of dinuclear units, both with two ZnL units bridged by two acetate anions but in three different bridging coordination modes. Their vibrational modes, absorption and photoluminescence properties have also been investigated.